Maternal serum tumour necrosis factor receptor 1 (TNF-R1) at 30–33 weeks in the prediction of preeclampsia. (21st March 2013) - Mosimann, Beatrice; Wagner, Marion; Birdir, Cahit; Poon, Leona C. Y.; Nicolaides, Kypros H.
Abstract: Objective: To investigate the potential value of maternal serum concentration of tumour necrosis factor receptor 1 (TNF-R1) at 30–33 weeks' gestation in the prediction of preeclampsia (PE) developing at or after 34 weeks. Methods: Serum TNF-R1 was measured at 11–13 and at 30–33 weeks' gestation in a case-control study of 50 cases that developed PE at or after 34 weeks and 250 unaffected controls. The measured values of TNF-R1 were converted into multiples of the normal median (MoM) and the MoM values in the PE and control groups were compared. Results: The median MoM TNF-R1 was significantly increased at both 11–13 weeks (1.094 MoM versus 1.003 MoM) and at 30–33 weeks (1.101 MoM versus 1.006 MoM). In screening for PE by a combination of maternal characteristics and serum TNF-R1 at 30–33 weeks, the estimated detection rates of PE at false positive rates of 5% and 10% were 32.0% and 40.0%, respectively. Conclusion: Screening by maternal characteristics and serum TNF-R1 at 30–33 weeks could be effective in identifying some of the cases that will subsequently develop PE.